EVALUASI PENERAPAN PERUBAHAN TARIF UMKM TERHADAP KETAATAN WAJIB PAJAK UMKM KOTA MAKASSAR - Akhmad Akhmad; Andi Arifwangsa Adiningrat; Karmila Oktafiana; Muhaimin Muhaimin (Universitas Muhammadiyah Makassar, 2020)
This study aims to answer the problem regarding the Application of Tariff Changes for Micro, Small and Medium Enterprises (MSMEs) to the compliance of the Makassar City UMKM Taxpayers. This research is a type of research that uses descriptive qualitative methods. This research data includes primary data and secondary data. The results showed that after implementing the policy of changing the MSME rate from 1% (PP 46 2013) to 0.5% (PP 23/2018) the level of taxpayer compliance has increased. This is evidenced by the increasing number of new taxpayers who register to obtain Taxpayer Identification Number (NPWP). The advantage felt by MSME players is that the tax imposed is now much lower than before. West Makassar KPP Pratama also benefited, as evidenced by the amount of tax revenue from West Makassar KPP Pratama in 2018 experiencing a significant increase.